INTERVENCIÓN DEL CARDENAL MERRY DEL VAL EN LOS NOMBRAMIENTOS DE OBISPOS ESPAÑOLES (1903-1914) - Cárcel Ortí, Vicente (Archivum historiae pontificiae, 1994)
Pendant le pontificat de Pie X (1903-1914), 70 évêques ont été nommés en Espagne. Le cardinal secrétaire d'État, l'espagnol Merry del Val, intervenu dans toutes les promotions, et il a essayé de recommander les candidats du Saint-Siège et de refuser ceux présentés par le Gouvernement. L'article analyse en particulier les difficultés survenues pour la nomination des évêques pendant la période 1910-1914, en raison des tensions du moment entre l'Église et l'État espagnol. During the pontificate of Pius X (1903-1914) the intervention of his Secretary of State, the Spanish Cardinal Merry del Val, was decisive for the 70 appointments of bishops made in Spain. Frequently he tried to promote the candidates of the Holy See, and to reject those presented by the Spanish government, not considering them suitable enough. The article also analyzes the difficulties encountered in making episcopal appointments between 1910 and 1914, due to strong tensions at that time between the Church and the State.